Impacto da pandemia de COVID-19 no tratamento cirúrgico e reabilitador de pacientes com fissuras labiopalatinas em hospital pediátrico - Francisca Thainá Machado Magalhães; Assis Filipe Medeiros Albuquerque; Larissa Loiola Batista (Residência Pediátrica)
OBJECTIVE: Analyze the impact of the COVID-19 pandemic on surgical and rehabilitative treatment of patients with cleft lip and palate. METHODOLOGY: This is a quantitative retrospective observational study. Based on data collection of surgical approach in the treatment of cleft lip and palate in pediatric patients assisted, in the pre and pandemic period between 2018 and 2021, on the Integrated Fissure Care Center. Three different strands were analyzed for a more in-depth overview: the number of new patients who arrived at the service from 2018 to 2021; the quantitative of rehabilitative surgical procedures performed during the same period; and the number of patients in completion of orthodontic treatment on hold for alveoloplasty with alveolar bone grafting. RESULTS: The importance of an integrated multidisciplinary team is indisputable, due to the complexity of patients; in addition to the indispensability of a standardized classification method for future surveys; the prevalence of males was observed; there was a decrease in the admission of new patients in the pandemic period and; a reduction in the total number of surgical procedures (cheiloplasty and palatoplasty) in the pandemic period, while alveoloplasty were completely suspended. CONCLUSION: The pandemic brought aggravating factors: a decrease in the number of patients seen; delay in arriving at the service; decrease in the number of surgical procedures; as a result, the treatment is carried out outside the ideal period, which leads to sequelae, mainly to speech. The impact reflects in consecutive years, with long queues and patients operated outside the ideal period.